DIGITAL TRANSFORMATION STRATEGIES FOR SMES TO ACHIEVE SUSTAINABLE BUSINESS IN THE INDUSTRY 4.0 ERA - Dony Hermawan (Journal of Innovation Research and Knowledge, 2026)
This study discusses digital transformation strategies for Small and Medium Enterprises (SMEs) to achieve sustainable business in the Industry 4.0 era. Digital transformation has become an essential strategy for SMEs due to rapid technological development, changing consumer behavior, and increasing market competition. This research uses a descriptive qualitative approach through a literature review method by analyzing various studies related to digital transformation, SMEs, digital strategy, competitiveness, and business sustainability. The findings show that digital transformation is not limited to the adoption of digital tools, but also involves changes in business strategy, operational processes, innovation capability, and entrepreneurial mindset. Key strategies include improving digital literacy, adopting e-commerce and digital payments, optimizing digital marketing, utilizing data for decision-making, strengthening innovation capabilities, and integrating sustainability principles into business operations. Digital transformation contributes to economic sustainability by improving efficiency, productivity, profitability, and market access. It also supports social and environmental sustainability through better resource management, inclusive business practices, and reduced operational waste. Therefore, a structured and sustainable digital transformation strategy is crucial for SMEs to enhance competitiveness, resilience, and long-term business sustainability in the Industry 4.0 era